THE EFFECT OF AMINO ACID COMPOUNDS IN FERMENTED SOYBEANS AGAINST FIBROBLAST GROWTH FACTOR IN MICE PANCREATIC Î²-CELLS FIGURES - Dharma, Surya; Almasdy, Dedy; Dillasamola, Dwisari; Rasyid, Roslinda; Wahyuni, Dianty Dwi; Afifi, Fadhilah (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study is to determine the effect of the amino acid compound in fermented soybeans against fibroblast growth factor (FGF) in mice's pancreatic Î²-cell figures. This study was also done to know the effect of given combination of fertilized egg whites powder with tempe (Indonesian conventional food and the fermentation product of soybeans fermentation) in a dose of 7250 mg/kg. Methods: All of the experimental animals pancreases were designed to be damaged by given alloxan in a dose of 150 mg/kg, except for the negative control group without anything given. The experimental animals were divided into 7 groups which consist of the negative control group, positive control group, and the rests 5 group of FGF test preparation in dosages of 100; 140; 200; 300; and 425 mg/kg combined with fermented soybeans in a dose 7250 mg/kg. This experiment was conducted for 21 days, observed at 7th, 14th, and 21st day. The data analysis used is a statistical test of one-way analysis of variance (ANOVA) and two-way ANOVA. Results: The result showed a significant decrease in blood glucose levels (p<0.05) in mice for all treatments when compared with positive controls. From the result of the histopathologic examination, pancreatic Î²-cells improve utterly close to the control condition (-). In the qualitative immunohistochemical examination, there was a difference in the stained pancreatic Î²-cells marked by yellow density. Meanwhile, the quantitative observation did not show any improvement against normal condition control (-) (p<0.05). Conclusion: The combination of egg whites and fermented soybean significantly decreased the blood glucose levels, and the occurrence of the Langerhans island cells was nearly normal.